PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) MEMODERASI PENGARUH LIKUIDITAS, PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan LQ45 yang terdaftar di Bursa Efek Indonesi a tahun 2013 -2016) - Angraini, Eka Wahyuningsih; Sunarto, Sunarto (Jurnal Ilmiah Telaah Manajemen, 2018)
The purpose of this study is to analyze the Disclosure of Corporate Social Res ponsibility which moderate the influence of Liquidity, and Profitability to Firm Value study on LQ 45 companies listed on Indonesia Stock Exchange year 2013-2016. The research used purposive sampling method for sampling. Data obtained by publication www.idx.co.id. A sample of 158 companies were listed in LQ45 on the Indonesia Stock Exchange. The analysis technique used is multiple regression analysis. Based on statistical test F shows that Liquidity has a significant negative effect on Corporate Value, Pro fitability has a significant negative effect. While the moderation of Corporate Social Responsibility moderated results are significantly positive, and Profitability moderated by Corporate Social Responsibility results negatively. The result of analysis shows that the prediction ability of independent variable Liquidity and Profitability to Company Value is 27,0% indicated from Adjusted R2 amount and the rest equal to 63% influenced by other variable outside model. As for the variable value of Company R2 29 .2% which means that the large variation of Company Value variables that can be explained by independent variables while the remaining 70.8% influenced by other variables outside the research model. Keywords : Liqudity, Profitability, Corporate Social Res ponsibility, Firm Value